Family Planning Behavior and Small Family Concept Acceptance in Two Different Geographical Characteristics Municipality of South Klaten, Klaten, Central Java - P Priyono (Forum Geografi, 1992)
The research aim to know the family planning behaviour, the acceptance small family norm and the influential factors in two villages that have different geographical aspect. The behaviour involve the knowledge, the attitude and the practice where as the influential factors involve education, accupation, values of children, income, children still born and family size desired. The research areas are chosen purposive in two villages that have different geographical aspect, social aspect and cultural aspect. The aspect are: 1) location and topography, 2) socialy  structure, and 3) the achievement of effective acceptor. Based on the three aspects, Ngalas village (developing) and Sumberejo (developed) are chosen as research areas. The recorded as ative acceptor (recordedin RI/PUS/1991 form). The respondents are chosen by cencus at two neighborhoord association at every village. There are six variables in this research are assumed influence the periode of the contraceptives use, such as education, occupation status, values of children, family income, children still born, and family size desired. There are three variables are assumed influence the small family norm, such as education, occupation status, and values of children. The data was analyzed by frequency table, crosee table, and statistical analysis (Q square and Regresion). The data was always compared between the two villages. The analysis use computer by Microsoft Program. The research result showed that Sumberejo was better than Ngalas in the knowledge, the attitude, and the practice of family planning. Most of the people who live in Sumberejo understood the contraception device well (52,4%), where as in Ngalas (26,8%). Both of them agreed on using contraception device (more than 70%). The respondent who live in Sumberejo used IUD (40%) and MOW/MOP (23,23%). They had used of the contraception device for 4.8 years on an average. Mean  while the respondents in Ngalas use IUD (23,68%) and MOW/MOP (2,63%). They had used the contraception device for 3,8 years on an average. With respect to decision making of family planning. Sumberejo was better than Ngalas (Sumberejo: 83,4% and Ngalas 63,64%). The purpose of family planning has achieved birth stop. Sumberejo achieved 73,33% and Ngalas achieved 54,55%. The research result showed that the both Sumberejo and Ngalas accepted small family norm. Values of children  were heigh (Sumberejo 97,57% and Ngalas 93,31%). It indicates that the parent still hope the children role for their family. Not only did the parent hope from economics aspect but they hoped from non economic aspect as well. Both the average of live birth and the children who still alive in Sumberejo was lower than Ngalas. Mean while the number of the children who were desired was 2,9 child in Sumberejo and 2,8 in Ngalas. Based on seven statement that was used to identify the small family, there was tendency that the respondent in Sumberejo had better attitude than Ngalas about small family. The factor that influence the period of the contraception device was the number of the children who still children, income, and family planning norm did not influence the period of using of contraception device. The influential factors in acceptance of small family was education. The higher education the better aception of small family norm. Values of children also influenced the acceptance of small family norm, but there was difference of the direction between Sumberejo and Ngalas. In Sumberejo the higher occupation the better aceptance of small family norm, but in Ngalas, the higher percentance occupation the lower acceptance of small family norm.